“First I was an explorer; then I was an artist.” Robert J. Flaherty som fotograf - Skare, Roswitha (Nordlit, 2015)
Robert J. Flaherty is today best known for his films, and especially for his first film Nanook of the North (1922). In discussions about the early years of Flaherty’s career there has been much emphasis on Flaherty as a man with little formal education, a self- made man and an explorer. Flaherty’s statement “First I was an explorer; then I was an artist” is quoted over and over again. In this article I take a closer look at the early years of Flaherty’s career, the years before the premiere of Nanook and his reputation as a filmmaker. I discuss the photographs taken by Flaherty on his first expeditions in the years before 1915 focusing on the use and reuse of these photographs in different contexts like newspapers, journals and books. Finally, I also discuss whether these photographs, and especially two of the portraits that are used repeatedly, are only ethnographic or artistic as well.